Saul's Demise, David's Lament, and Custer's Last Stand - Barrick, W. Boyd (Journal for the study of the Old Testament, 1997)
Many readers, beginning with Josephus (Ant. 6.4.343-50), perceive the death of Saul as narrated in 1 Sam. 31 (1 Chron. 10).1-6 to be heroic or otherwise ennobling, a courageous but doomed 'last stand' in defense of his people. P.K. McCarter in par ticular finds this characterization also in the lament, translating 2 Sam. 1.19a 'Alas, prince of Israel [= Saul] slain standing erect', the pose evocative of bravery. This characterization, however, is a case of eisegesis spawned by the workings of the 'Martyred Hero' paradigm in the reader's mind and readerly imagination. This paradigm, identified by folklorist B.A. Rosenberg, is typified by the American popu lar legend of 'Custer's Last Stand' which envelops the death of Lt. Col. George Armstrong Custer at the Battle of the Little Bighorn (25 June 1876). Without this external and perhaps culturally anachronistic template, the ancient Hebrew narrative is seen to represent Saul's death as cowardly and disgraceful. McCarter's mgenious treatment of 'al bāmôteykâ hāllāl in 2 Sam. 1.19a (and 1.25b) is rejected on philolo gical and literary grounds in favor of 'slain upon thy back', originally proposed by D.N. Freedman in 1964. It is doubtful whether these materials yield anything sub stantive about the actual circumstances of Saul's death—assuming, of course, that Saul actually existed.